The impact of undetected hearing loss and ear diseases on academic performance among standard 6 students of Sekolah Kebangsaan Kubang Kerian 3 - Habib, Syarifah Najihah Tuan (2010)
To determine the prevalence of hearing impairment and ear diseases in standard 6 students of Sekolah Kebangsaan Kubang Kerian 3 (SKKK3) and its association with academic performance. It was a cross-sectional study with follow-up, carried out at SKKK3, Kubang Kerian, Kelantan in 2008. Distortion Product Otoacoustic Emission (2, 3, 4 and 5 kHz) and Otological Examination were perform in first stage for the purpose of screening the presence of hearing loss. Participants that failed the first stage will undergo secondary screening which was Pure Tone Audiometry (0.25 to 8 kHz). Participant’s hearing level was compared with their learning performance using three methods: class streaming based on year-end assessment, Ujian Pencapaian Sekolah Rendah (UPSR) results and Bahasa Melayu UPSR results. From overall 232 standard six students, only 193 students participated in this study and were screened in the first stage. The prevalence of ear diseases was 15% (29 participants). Impacted wax was the commonest ear disease found (8.8%) followed by chronic suppurative otitis media (2.6%). For the hearing impairment, the prevalence of hearing impairment by primary screening with OAE test and otological examination was 9.8% but following the secondary test with PTA, the prevalence was 10.3%. After intervention with repeat OAE,